Crisis management during anaesthesia: awareness and anaesthesia. Issue 3 (2nd June 2005) - Osborne, G A; Bacon, A K; Runciman, W B; Helps, S C
Abstract : Background: Patient awareness during general anaesthesia has considerable potential for severe emotional distress in the patient as well as professional, personal, and financial consequences for the anaesthetist. Objectives: To examine the role of a previously described core algorithm "COVER ABCD–A SWIFT CHECK", supplemented by a specific sub-algorithm for awareness, in the detection and management of potential awareness in association with general anaesthesia. Method: The potential performance of this structured approach for each of the relevant incidents among the first 4000 reported to the Australian Incident Monitoring Study (AIMS) was compared with the actual management as reported by the anaesthetists involved. Results: Of the first 4000 reports received by AIMS, there were 21 incidents of patient awareness under general anaesthesia, and 20 of patients being paralysed while awake from "syringe swaps" before induction of anaesthesia. In 12 of the 21 reports there was an obvious cause, most commonly a low concentration of volatile agent (8 of 12 reports). The AIMS "core" crisis management algorithm would have detected the cause of awareness in all of these cases. In nine reports the course of anaesthesia appeared unremarkable, and in these the algorithm would not have been expected to detect or prevent awareness. Volatile agent monitoring would have prevented some cases of awareness, as would bispectral index electroencephalographic (BIS) monitoring. The role of BIS monitoring is still contentious, but it should be considered for high risk patients. Conclusion: Awareness should be minimised by thorough checking of equipment, particularly vaporisers, and frequent application of a structured scanning routine. Awareness may occur during crisis management and aftermath protocols should include patient follow up to detect and manage awareness when it occurs.